STUDENTS’ READING TECHNIQUES DIFFICULTIES IN RECOUNT TEXT - Ayu Sonia Habibah Fisher (Journal of English and Education, 2016)
This study aims to investigate the students’ reading techniques difficulties in recount text. The study is based on the theory proposed by Mikulecky and Jeffries (2004) regarding the reading techniques; previewing and predicting, scanning, skimming, summarizing and making inference. The study employed qualitative approach with a case study design. Fifteen students in the sixth semester of a state of University in Bandung were selected as the participants of the study. Reading test and semi-structured interview were used as the instruments. The data from the reading test in the form of students’ responses were analyzed based on the scoring guide of reading techniques (adapted from Mikulecky and Jeffries, 2004). The findings of the study indicated that the most difficult reading technique is making inference. It can be seen that 53% of the students get a lower score. Based on the findings, it is suggested that English teachers put a big concern in developing students in being a good reader and giving a guidance in practicing the techniques.